Cost Control Analysis Using the Earned Value Method on the Warehouse Construction Package and its Supporting Facilities at Juwata Airport - Imaniar, Ridha Annisa; Witjaksana, Budi; Purnama, Jaka (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The construction of warehousing and supporting facilities at Juwata Airport has several obstacles that cause delays in the implementation of the work, so a work control method is needed, namely the earned value method by assessing the cost and time performance of project implementation such as Cost Variance (CV), Schedule Variance (SV), Schedule Performance Index (SPI), and Cost Performance Index (CPI) as well as the estimated cost and time of project completion. The purpose of this research is to calculate the amount of cost needed to complete the project of Warehousing Development Package and Supporting Facilities of Juwata Airport on time according to the plan schedule. The method used is the Earned Value Method in evaluating cost performance and time performance. The analysis carried out uses 3 (three) indicators, namely ACWP (Actual Cost of Work Performance), BCWP (Budgeted Cost of Work Performance) and BCWS (Budgeted Cost of Work Scheduled). By using the earned value method, the final project cost estimate obtained from the EAC is Rp. 15,019,062,678.43 and the estimated time / Time Estimate (TE) at week 26 shows 239 calendar days so that the completion time is 28 days late from the contract schedule. And the solution to the delay is to accelerate the work with an additional cost of Rp. 68,970,000. Future research should explore optimization strategies to enhance efficiency in cost estimation and project scheduling.